Perfil do envelhecimento da população idosa do município de Arapongas, Paraná - Stefanuto, Graziela (2010)
This study aims to get to know the profile of the elderly population of the town of Arapongas-PR. We analyzed the main causes of morbidity the mortality in the period 1996-2006, according to sex, age and cause according to the International Classification of Diseases, 9th and 10th Reviews, using the databases of SIM, SIH and also of the Ministry of Health. There was an increase related to the total of deaths in the elderly with emphasis on the percentage of hospitalizations in elderly males; overmortality in elderly females in relation to older males, especially above 75 years of age, with main causes of death in descending order: circulatory diseases, neoplasia, respiratory system diseases, endocrine diseases, nutritional and metabolic and external causes. Regarding the main causes of hospitalization among the elderly of both sexs, there are, in descending order: circulatory system diseases, diseases of the respiratory system, and diseases of the digestive system, except for the fourth question: neoplasia (elderly male) and external causes (elderly female). Getting to know the profile of aging remains a challenge for the whole society, especially in seeking to track and improve the quality of life of the elderly with public policies.